Etnoarchaeological approach to hunter-gatherers basketry of Tierra del Fuego-Patagonia (Chile and Argentina) - Franch Bach, Anna; Vietri, Luisa; Piqué Huerta, Raquel (Ethnobotany Research and Applications, 2025)
Background: Tierra del Fuego and the Oriental Channels of Patagonia in Chile and Argentina comprise a vast area of channels, fjords, and islands. In pre-European times, these areas were inhabited by hunter-fisher-gatherer communities who navigated in these channels in their canoes. The Isla Grande of Tierra del Fuego was also home to pedestrian hunter-gatherers. Skilled basket making was a notable craft among the women of these groups, and some of these traditional techniques persist today. Methods: Our research delves into the ethnohistorical documentation and ethnographic collections housed in various museums across Chile, Argentina, and Europe. The primary goal is to address several questions concerning the ecological and technical knowledge of these populations and the purpose of their organic containers. The outcomes of our investigation shed light on the diverse aspects of baskets, including variations in shapes, raw materials, sizes, and production techniques. Results: Notably, our findings underscore the relationship between these variables and the function of the containers. The predominant use of these baskets was for transporting and storing food and belongings. Remarkably, there is a homogeneity in the raw material employed (Marsippostermum grandiflorum) and a noticeable low diversity in terms of shapes and technic. Its geographical origins and their significance within these hunter-gatherer-fisher societies are also discussed, in particular intergenerational transmission of knowledge. Keywords: Basketry, rushes, Hunter-fisher-gatherers, Patagonia-Tierra del Fuego, ethnoarchaeology.